EXISTING TRENDS OF HERITAGE CONSERVATION IN SHIMLA: A HILL TOWN IN INDIA - Bansal, Kanika; Chhabra, Pankaj (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India is bestowed with rich cultural diversity manifested by a wide range of tangible heritage resources. The formal inception of the Archaeological Survey of India (ASI) during colonial rule paved way for heritage conservation protecting the National Monuments pan India that are less than 0.01% of the total existing heritage resources. Though the State Archaeology Department and the National Monuments Authority have taken various initiatives at the state levels, the adopted conservation process lacks an integrated approach due to the involvement of a wide array of stakeholders ranging from the Central Government to the local authorities to the various conservation groups. Each of these agencies employs vivid funding sources and mechanisms and variable sets of guidelines and norms with diversity in delivery models for various heritage conservation projects limiting the conservation process to piecemeals. Shimla, a colonial hill town in the north of India, and the state capital of Himachal Pradesh is home to vast stock of tangible and intangible heritage resources. Amidst rapid growth and urbanization, over the past two decades, several initiatives have been taken by the state government of Himachal Pradesh (GoHP) in resonance with the urban local bodies of Shimla but only a few of the conservation projects have seen success. However, the findings of the research bring out that though the GoHP has been proactive in protecting its heritage resources, however, a large part of the heritage resources in Shimla remain in a state of neglect and lack maintenance and management. This is because of the complexity involved in the conception and implementation of heritage conservation because of the vastness of heritage resources and the involvement of diverse groups of stakeholders in the process, as the role of urban local bodies directly impacts the efficiency of the conservation program. The study brings out the heritage conservation process adopted in Shimla by various government agencies.